Development of Management System for eduroam Database Updated Specification - Petrosyan, Arthur S.; Petrosyan , Gurgen S. (Mathematical Problems of Computer Science, 2020)
This paper presents a system developed to simplify the eduroam database management. The goal of the eduroam database is to provide the necessary information needed for the operation of the eduroam service and related supporting services like eduroam monitoring, service location maps and usage statistics, as well as the eduroam CAT tool. eduroam database specifications have been updated to the second version and the update has recently become mandatory, requiring many changes for databases of all National Roaming Operators (NRO). The solution presented here can be useful for NRO administrators to simplify the eduroam database management.